STRONTIUM CHLORIDE INDUCED PARTHENOGENETIC OOCYTE ACTIVATION AND EMBRYONIC DEVELOPMENT IN BUFFALOES - D. Reena; S. Balasubramanian; D. Gopikrishnan; A. Palanisammi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Artificial oocyte stimulation is essential for assisted reproductive technologies like Somatic Cell Nuclear Transfer (SCNT), Intracytoplasmic Sperm Injection (ICSI). In this study, we examined the ability of strontium Chloride (Sr2+) to induce activation and in vitro embryonic development in buffalo oocytes in combination with Cytochalasin B and 6- dimethyl aminopurine (DMAP). Matured buffalo oocytes (n=276) were activated with 10 µM Sr2+ and 5 µg/ml cytochalasin B (Group I) for 2.5 hrs. In group II, 266 matured oocytes were activated with 10 µM Sr2+ and 5 µg/ml cytochalasin B for 2.5 hrs followed by culture in 2 mM 6-DMAP for 4 hrs. The activation rate for group I was significantly higher (P < 0.01) than for group II (38.35±1.00% and 31.29±0.90%, respectively). However, no significant difference was observed in morula development (9.57±0.84% and 6.80±0.59%, respectively). In conclusion, it is practicable to use Sr2+ in combination with cytochalasin B for parthenogenetic embryo production in buffalo.